APPROXIMATE ANALYTICAL SOLUTIONS OF NONLINEAR HYPERBOLIC PARTIAL DIFFERENTIAL EQUATION - Che Haziqah Che Hussin; Suriana Lasairaya; Arif Mandangan; Darmesah Gabda (Journal of Islamic, Social, Economics and Development, 2022)
The Multistep Modified Reduced Differential Transform Method (MMRDTM) isproposed and implemented in this study to obtain solutions of hyperbolic partial differentialequations. We examine at the nonlinear Schrodinger equation (NLSE). Prior to implementingthe multistep strategy, we switched the nonlinear term in the NLSE with the correspondingAdomian polynomials using the proposed technique. As a result, we can acquire solutions forthe NLSE in a simpler and less difficult manner. Furthermore, the solutions can be estimatedmore precisely over a longer time period. We studied the NLS equation and graphed thefeatures of this solution to show the strength and accurateness of the proposed technique.